If it's not what You are looking for type in the equation solver your own equation and let us solve it.
24=2(n+7)
We move all terms to the left:
24-(2(n+7))=0
We calculate terms in parentheses: -(2(n+7)), so:We get rid of parentheses
2(n+7)
We multiply parentheses
2n+14
Back to the equation:
-(2n+14)
-2n-14+24=0
We add all the numbers together, and all the variables
-2n+10=0
We move all terms containing n to the left, all other terms to the right
-2n=-10
n=-10/-2
n=+5
| 2x^2-18x-50=0 | | 26-x=60.0 | | 2x+4+-6x=24*5 | | -9.6x+1.8=123 | | 2x+4+-6x=24•5 | | Y=-2|x-3|-4 | | -3x-2=58 | | 2x+4+-6x=24 | | 4y^2=120 | | 8(x+3)=70 | | 16=x/4+14 | | 1/4x^2-1/8x=15/8 | | (x+2)^2+11(x+2)+24=0 | | -X+9+3(x-2)=5 | | 4x+23=109 | | 8y+34=44 | | 2x-10+4x=-3 | | 3(6-n)=-3n+18 | | 75–7.5x=4x+6 | | -2(x+12)=23 | | x/3+1/2=×/6-5/12 | | 15=u/2+8 | | 6g-4=2g | | 2y+66+40=180 | | 16y+9=-4 | | -2x-2(17+9x)=14 | | 2w-5w+4=-14 | | M+5m=2 | | 10=7w-8 | | 2=x/4−7 | | -2g+6=9 | | 7b+27+3b+7=180 |